What is strategic management research? - Rozanna, Mira; Ahadiat, Ayi (goodwood publishing, 2023)
Purpose: The aims of this study is to describe the strategic in management research Methods: A literature analysis method was used, in which researchers conduct conceptual studies and review strategic and strategic management theories, research results, and expert opinions. Furthermore, the researchers grouped, allocated, organized, and used a variety of literature in specific fields. Results: Strategic management is a concept of building capabilities that enable companies to create value, shareholders, and society when operating in a competitive market. This can result in studies of decisions and actions taken by top executives/TMT so that companies gain competitive advantage. Limitations: This study used a qualitative approach with a limited level of generalization; therefore, so in the future it may also be necessary to review it with other approaches and wider research locations. Contribution: This study provides views on the revitalization of tourism destinations in terms of synergy between stakeholders so that it can be the basis for developing development policies, especially in the aspect of local communities.